Impact of the host on Toxoplasma stage differentiation - Carsten G.K. Lüder; Taibur Rahman (Microbial Cell)
The unicellular parasite Toxoplasma gondii infects warm-blooded animals and humans, and it is highly prevalent throughout the world. Infection of immunocompetent hosts is usually asymptomatic or benign but leads to long-term parasite persistence mainly within neural and muscular tissues. The transition from acute primary infection towards chronic toxoplasmosis is accompanied by a developmental switch from fast replicating and metabolically highly active tachyzoites to slow replicating and largely dormant bradyzoites within tissue cysts. Such developmental differentiation is critical for T. gondii in order to complete its life cycle and for pathogenesis. Herein, we summarize accumulating evidence indicating a major impact of the host cell physiology on stage conversion between the tachyzoite and the bradyzoite stage of the parasite. Withdrawal from cell cycle progression, proinflammatory responses, reduced availability of nutrients and extracellular adenosine can indeed induce tachyzoite-to-bradyzoite differentiation and tissue cyst formation. In contrast, high glycolytic activity as indicated by increased lactate secretion can inhibit bradyzoite formation. These examples argue for the intriguing possibility that after dissemination within its host, T. gondii can sense its cellular microenvironment to initiate the developmental program towards the bradyzoite stage in distinct cells. This may also explain the predominant localization of T. gondii in neural and muscular tissues during chronic toxoplasmosis.